Yield of 'Royal Gala' apple trees in response to pruning before or after leaf drop - Almeida, Gustavo Klamer; Fioravanço, João Caetano (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to evaluate different pruning times, performed before or after natural leaf drop, regarding their effects on the yield of 'Royal Gala' apple (Malus domestica) trees. The experiment was carried out in Vacaria, in the state of Rio Grande do Sul, Brazil, on seven-year-old trees in four harvests from 2008/2009 to 2011/2012, using a randomized block design. The following pruning times were tested: 46 days before leaf drop (DBLD); 25 DBLD; 5 DBLD; 15 days after leaf drop (DALD); 36 DALD; 55 DALD; and 75 DALD. All pruning times before natural leaf drop reduced yield per tree and fruit set. Among the pruning times before leaf drop, 46 DBLD resulted in the lowest yield. Pruning performed after natural leaf drop, still during dormancy, resulted in a higher yield per tree, in comparison with pruning times before leaf drop. The effect of pruning times on average fruit mass, pulp firmness, content of soluble solids, titratable acidity, and soluble solids/titratable acidity ratio differed between harvest years. Pruning performed at different times, before natural leaf drop, causes yield reduction in 'Royal Gala' apple trees, and the pruning time at 46 DBLD results in the lowest yield.
Keywords: Malus domestica; fruit set; pruning time